Systemic messenger RNA as an etiological treatment for acute intermittent porphyria. (December 2018) - Jiang, Lei; Berraondo, Pedro; Jericó, Daniel; Guey, Lin; Sampedro, Ana; Frassetto, Andrea; Benenato, Kerry; Burke, Kristine; Santamaría, Eva; Alegre, Manuel; Pejenaute, Álvaro; Kalariya, Mayur; et al.
Abstract Acute intermittent porphyria (AIP) results from haploinsufficiency of porphobilinogen deaminase (PBGD), the third enzyme in the heme biosynthesis pathway. Patients with AIP have neurovisceral attacks associated with increased hepatic heme demand. Phenobarbital-challenged mice with AIP recapitulate the biochemical and clinical characteristics of patients with AIP, including hepatic overproduction of the potentially neurotoxic porphyrin precursors. Here we show that intravenous administration of human PBGD (hPBGD) mRNA (encoded by the geneHMBS ) encapsulated in lipid nanoparticles induces dose-dependent protein expression in mouse hepatocytes, rapidly normalizing urine porphyrin precursor excretion in ongoing attacks. Furthermore, hPBGD mRNA protected against mitochondrial dysfunction, hypertension, pain and motor impairment. Repeat dosing in AIP mice showed sustained efficacy and therapeutic improvement without evidence of hepatotoxicity. Finally, multiple administrations to nonhuman primates confirmed safety and translatability. These data provide proof-of-concept for systemic hPBGD mRNA as a potential therapy for AIP. Systemic administration of human PBGD mRNA encapsulated in lipid nanoparticles ameliorates disease phenotypes in mouse and rabbit models of acute hepatic porphyria and is safe in nonhuman primates.